A challenging chairmanship in turbulent times. Issue 1 (2nd January 2021) - Cela, Margrét; Hansson, Pia
ABSTRACT: At a time of increased tension in the Arctic region, the smallest Arctic Council member state, Iceland, was handed the gavel. Following the reluctance of the US to include any mention of the effects of climate change in the Arctic, the Arctic Council Ministerial in Rovaniemi came to an end without a Declaration in 2019. Under the uncontroversial but also highly ambitious slogan Together Towards a Sustainable Arctic with a focus on the Arctic marine environment, climate and green energy solutions, people and communities of the Arctic and a stronger Arctic Council, the Icelandic chairmanship was faced with numerous challenges. Chairing the Arctic Council is on any day a challenge for a small state like Iceland with a limited foreign service. However, the effects of a world-wide pandemic limiting in-person communications and creating new technical and economic challenges, on top of the increased tension and the return of big power politics in the area, made it even harder. In this paper, we explore the Icelandic chairmanship of the Arctic Council and evaluate the challenges posed by external factors such as geopolitical and security developments in the Arctic as well as the effects of an unexpected global pandemic on a small state chairmanship. In spite of the growing tension between the two largest Arctic states, the US and Russia, in the last days of the chairmanship, the Reykjavik Arctic Council Ministerial concluded with both a declaration and the first-ever 10-year strategic plan, adopted in recognition of the Arctic Council's 25th anniversary.